(untitled) (Journal of the College of Basic Education, 2022)
Ethics lies as the basis on which society is built, and bears lofty values with which nations are raised and developed. Ethics is the true essence of our Islamic civilization throughout the ages. History bears witness to the best moral images it provided for human societies, but now the Islamic reality is undergoing many changes that made some of its sons Conscience leaves him, loss, cooperation, cohesion, and harmony among his sons, and it was only that he lost his moral value and followed his whims, so the Muslims retreated after they were in the shoulder of Islamic civilization and lived in the forms of development and urbanization, which raised its banner across the earth, and whose slogan was human morals, and by which it persevered. Ages are based on self-refinement and self-discipline, and finding happiness in this world and the hereafter, and this is what distinguished it from other civilizations that wear the robe of morality and raise slogans in the name of freedom. The Muslim is only to return to his religion, as it is a mirror of morals, the goal and the goal that he aims at to win the pleasure of God Almighty.